2008
DOI: 10.1016/j.neulet.2008.03.074
|View full text |Cite
|
Sign up to set email alerts
|

Spinal injection of IL-2 or IL-15 alters mechanical and thermal withdrawal thresholds in rats

Abstract: IL-2 and IL-15 were tested for effects on responses to mechanical or thermal stimuli when spinally administered to male Sprague-Dawley rats with surgically implanted intrathecal catheters. Restricted doses of both IL-2 and IL-15 produced increased responsiveness to mechanical stimulation of the hindpaws. This effect lasted up to 48 hours. IL-2 had biphasic effects on thermal responses whereas IL-15 produced thermal hypalgesia alone. These effects dissipated within 24 hours. These results suggest that IL-2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…In the mouse, intraperitoneal administration of IL-2 enhances the amnesic effects of scopolamine (76). In rats, spinal IL-2 injections enhance hindpaw responses, with biphasic effects on thermal responses, indicating that IL-2 modulates hyperalgesia (77). Plasma IFNc and IFNc-induced pathways are associated with hyperalgesia and chronic fatigue following Epstein-Barr virus and Parvovirus B19 infection (78,79).…”
Section: Resultsmentioning
confidence: 99%
“…In the mouse, intraperitoneal administration of IL-2 enhances the amnesic effects of scopolamine (76). In rats, spinal IL-2 injections enhance hindpaw responses, with biphasic effects on thermal responses, indicating that IL-2 modulates hyperalgesia (77). Plasma IFNc and IFNc-induced pathways are associated with hyperalgesia and chronic fatigue following Epstein-Barr virus and Parvovirus B19 infection (78,79).…”
Section: Resultsmentioning
confidence: 99%
“…Intraplantar administration of IL-2 in the naïve hindpaw [38] and intrathecal injection post nerve injury [39] increased the time until paw withdrawal upon application of radiant heat. On the other hand, a different series of studies showed a dose-dependent effect of intrathecal IL-2 in naïve rats: a low dose increased heat sensitivity, while a higher dose decreased sensitivity [40]. In addition, the lower dose of IL-2 increased mechanical sensitivity, while the higher dose had no effect [40].…”
Section: Nociceptive Actions Of Cytokinesmentioning
confidence: 99%
“…On the other hand, a different series of studies showed a dose-dependent effect of intrathecal IL-2 in naïve rats: a low dose increased heat sensitivity, while a higher dose decreased sensitivity [40]. In addition, the lower dose of IL-2 increased mechanical sensitivity, while the higher dose had no effect [40]. IL-15 has been proposed as a pro-inflammatory cytokine that supports immune infiltration, with possible implications in the development of pain [41].…”
Section: Nociceptive Actions Of Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Il-2 and IL-8 have been less consistently associated with pain, though each has been investigated in experimental or chronic pain conditions. IL-2 has been demonstrated to have both hyperalgesic and analgesic properties in rodent models, dependent on location and route of administration (Song et al, 2002; Cata et al, 2008). In one study, the concentration of IL-8 was found to be higher in plasma samples from OA patients than controls (Mabey et al, 2014), and another study found higher levels of IL-8 mRNA expression from synovial biopsies in OA patients than patients with meniscal tears (Nair et al, 2015), but other studies have failed to show a strong relationship between IL-8 and pain.…”
Section: Discussionmentioning
confidence: 99%